INOVASI KELESTARIAN SERANGGA PENYERBUK SEBAGAI UPAYA PENINGKATAN PRODUKSI KELAPA SAWIT DI DESA NEGARA TULANG BAWANG KECAMATAN BUNGA MAYANG KABUPATEN LAMPUNG UTARA - Shifa Usodri, Kresna; Utoyo, Bambang; Gusta, Adryade Reshi; Widiyani, Dimas Prakoswo; Hartono, Joko S S; Same, Made (Jurnal Pengabdian Nasional, 2022)
The people in Negara Tulang Bawang Village have a livelihood as farmers, civil servants, TNI,POLICE and private employees, entrepreneurs and traders as big as, workers as big as and others.The partner's great desire is that the gardens in the village can become pilot gardens and agro-tourismby applying technology and innovations that are useful for the production and productivity of plantationcrops. The innovation that can be applied is the procurement of innovation or technology for thepreservation of oil palm pollinating insects. The condition of the partners has a large area of land andabundant resources, but the productivity and production of palm oil is stagnant. The results of fieldreviews and discussions with partner farmers found that the presence of pollinating insects wasminimal at the location and assistance such as counseling and additional insight were not obtained bypartner farmers. The activity proposer team has designed the method of activity that is applied bymeans of counseling, demonstration, training, consultation, and guidance, as well as evaluation. Aftercounseling, assistance is carried out by monitoring and evaluating innovation programs that are givenor applied to farmers. Increased understanding and technical manufacturing of technology by 100%,implementation by 40% and increase in oil palm production after the implementation of technologytransfer by 21.43%.